Digital Insurance:A Case Study of Saudi Insurance Sector - Zayed, Mohmmad; Elashkar, Elsayed; Shoukry, Alaa; Hassan, Hebatalla (The Arab Journal of Administration, 2019)
Digital transformation is considered one of the challenges facing the insurance sector in the Kingdom of Saudi Arabia to comply with 20 0 vision. In addition to exploring the factors influencing this transfor- mation and the attittude of Saudi insurance companies towards adopting e-service approach, the quaity of the e-services offered by insurance companies, if any, were ivestigaed through a survey of the opinions of the policyholders. Results of the statisical analysis through regression, effect analysis annd ANOVA showed that the digital transformation by Saudi insurance companies still needs to be significantly improved in terms of the scope and diversity of services and that the success of this is significantly related to the quality of e-service realized by insurance customers. Results also revealed that insurance customers’ perceptions toward the quality of e-services differ according to age and educational level. It was recommended that Saudi insurance companies need to promote the culture of digital transformation among empolyees and customers as well as enhacing the scope and quality of e-services according to the priorities indicaed by the resuls, especially in terms of ensuring the quality of the website content, website safety and reliability and technical support.